EXPOSURE ANALYSIS OF NOISE INTENSITY IN THE MANUFACTURING AREA AT THE JOB TRAINING AND DEVELOPMENT CENTER SERANG - Ula, Shofiatul; Listijorini, Erny; Susilo, Sidik; Fakhrizal (DINAMIS, 2023)
Machines in manufacturing areas often cause noise. The noise comes from machine tools such as lathes, milling machines, grinder machines, and other tools that cause sound and vibration so they are prone to causing physical and psychological disorders. This study was to determine and analyze the noise level in three areas and ten points in the manufacturing room of The Job Training and Development Center Serang by the Regulation of the Minister of Manpower and Transmigration of the Republic of Indonesia Number PER.13/MEN/X/2011 with the maximum noise limit that has been set is 85 dBA. As for the results of the ten points, there is a point that exceeds the threshold value, namely at point 6 (85.8) dBA in the lathe area. Every operator in the manufacturing room that has a noise level that exceeds the threshold value must wear personal protective equipment in the form of earplugs or ear muffs that have been provided by the workshop to reduce the noise level.